A three-dimensional MnO2/graphene hybrid as a binder-free supercapacitor electrode1. Issue 104 (11th November 2015) - Xiong, Chuanyin; Li, Tiehu; Khan, Muhammad; Li, Hao; Zhao, Tingkai
<x xml:space="preserve">Abstract</x> Highly aligned manganese dioxide (MnO2) nanowall arrays electrodeposited onto Ti sheets are used as substrates to grow graphene (GR) through chemical vapor deposition (CVD), thus forming a three-dimensional (3D) MnO2/GR hybrid composite.